Safety and feasibility of robotic-assisted thoracic surgery after neoadjuvant chemoimmunotherapy in non-small cell lung cancer - Zeng, Jun; Yi, Bin; Chang, Ruimin; Chen, Yufan; Yu, Zhongjie; Gao, Yang (Frontiers in Oncology, 2023)
Objectives This study aimed to evaluate the safety and feasibility of robotic-assisted thoracic surgery (RATS) after neoadjuvant chemoimmunotherapy in NSCLC. Methods We retrospectively collected data for NSCLC patients who received thoracic surgery after neoadjuvant chemoimmunotherapy from May 2020 to August 2022. Surgery details, pathological response, and perioperative outcome were compared between video-assisted thoracic surgery (VATS) group and RATS group. Inverse probability of treatment weighting (IPTW) was used to equal the baseline characteristics. Results A total of 220 patients were divided into 78 VATS patients and 142 RATS patients. There was no 90-day mortality in either group. RATS patients demonstrated better results in conversion rate to thoracotomy (VATS vs. RATS: 28.2% vs. 7.5%, P < 0.001), number of lymph node stations harvested (5.63 ± 1.75 vs. 8.09 ± 5.73, P < 0.001), number of lymph nodes harvested (13.49 ± 9.325 vs. 20.35 ± 10.322, P < 0.001), yield pathologic-N (yp-N) assessment (yp-N0, 88.5% vs. 67.6%; yp-N1, 7.6% vs. 12.6%; yp-N2, 3.8% vs. 19.7%; P < 0.001), and visual analog scale pain score after surgery (4.41 ± 0.93 vs. 3.77 ± 1.21, P=0.002). However, there were no significant differences in pathological response evaluation for neoadjuvant chemoimmunotherapy (P = 0.493) and complication rate (P = 0.803). After IPTW-adjustment, these results remained constant. Conclusions RATS reduced the risk of conversion to thoracotomy, provided a better yp-N stage evaluation, and improved pain score; this suggests that RATS is safe and feasible for NSCLC patients after neoadjuvant chemoimmunotherapy.